Profiling Vocational School Students' Word Knowledge Level: A Study in Jakarta Timur - Wiranty, Glenda Mutia; Andang Saehu; Hanna Sundari; Mohammed H. Alaqad (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2024)
students are expected to acquire 2,000 to 3,000-word levels for general communicative purposes and 4,000 to 5,000-word levels or more for academic purposes. Nevertheless, only a few studies are refocusing on vocational school students. Therefore, this study descriptively analyzed the word knowledge level of vocational school students. This study was conducted online with 173 vocational school students in grades 10th and 11th. The result shows that above 70% of 173 participants successfully answered the 4,000 up to 5,000-word level, equivalent to K4 and K5 in vocabulary level. In contrast, the rest participants can answer the 1,000 up to 3,000-word level. The results indicate that the participants passed the requirements for communicative and academic purposed. This study also proposed the relevance of VLT results through post-graduate plans and gender diversity. The relevance becomes teachers’ consideration and recommendation to create meaningful and valuable teaching and learning materials based on their goals and needs.EFL students must acquire 2,000 to 3,000-word levels for general communicative purposes and 4,000 to 5,000-word levels or more for academic purposes. With such an enormous number of words, teachers must examine students’ word knowledge levels through the Vocabulary Level Test (VLT) before teaching and learning to determine relevant learning materials based on students’ needs and goals. Many related studies focus on senior school students. However, this study draws on vocational school students as they commonly work after graduation, and the ability to communicate with the English language is needed. Therefore, this study descriptively analyzed the result of the Vocabulary Level Test in 173 vocational school students majors. The result shows that more than in all 70% of participants successfully answered the 4,000 up to 5,000word level. Meanwhile, the rest of the participants could answer 1,000 to 3,000 words. The relevance of this study is the teachers’ consideration and recommendation to create meaningful and valuable teaching and learning materials based on their needs, as well as the students’ scores in VLT.